A numerical study on the hydrodynamic and heat transfer characteristics of oscillating Taylor bubble in a capillary tube. (5th October 2015) - Pattamatta, Arvind; Sielaff, Axel; Stephan, Peter
Abstract: In this paper hydrodynamic and non-phase change heat transfer characteristics of Taylor-Bubble (T-B) due to pressure induced oscillations is numerically investigated. The numerical method is validated with previous results for the simulation of unidirectional Taylor-Bubble flow and with in-house experimental data for adiabatic oscillatory T-B using FC-72 as the working fluid. A parametric study involving the effect of applied frequency of oscillation and bubble length on hydro dynamic and heat transfer characteristics of oscillatory T-B is carried out. From the bubble frequency study, it is observed that the average film thickness decreases with the oscillation frequency continuously. The time averaged Nusselt Number, Nu*, is found to be inversely proportional to the average film thickness. From the bubble length study, it is concluded that Nu* increases with increasing bubble length. The ratio of Nu* to the pressure drop across the capillary reveals an increasing trend with the bubble length at 5 Hz applied frequency while the opposite trend is observed at 50 Hz frequency. This has a significant impact on the heat transfer characteristics of pulsating heat pipes in which the oscillation frequency of T-B is less than 10 Hz. Highlights: Heat transfer characteristics of oscillatory Taylor-Bubble (T-B) are investigated. The average film thickness decreases with the oscillation frequency. Nusselt Number is found to be inversely proportional to film thickness. Nusselt Number is found to increase with T-B length.